INTEGRATING INTERCULTURAL COMMUNICATION INTO ENGLISH LESSONS: CHALLENGES, OPPORTUNITIES AND PRACTICAL SOLUTIONS - Makhmudova Muslimakhon Zokirjon qizi; Advisor Erkulova Feruza Melikuziyevna (Bright Mind Publishing, 2025)
In today’s interconnected world, the integration of intercultural communication (IC) into English lessons is crucial for preparing students to engage effectively in global contexts. As English is increasingly used as a global lingua franca, teaching not only the language but also the cultural contexts in which it is used has become essential for effective communication. Integrating intercultural competence into English lessons allows students to develop the necessary skills to engage with diverse cultures and navigate global interactions. However, the integration of IC into language teaching presents various challenges and opportunities that require careful consideration by educators and curriculum developers.
Keywords: Intercultural communication, cultural awareness, global competence, language education, inclusive curriculum, teacher training, educational challenges, practical strategies, critical thinking.